2015
DOI: 10.1111/edt.12201
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of severely traumatized teeth with immediate implants and immediate loading: literature review and case reports

Abstract: One of the options for management of severely traumatized dentitions is to provide immediate implant placement with immediate loading. Three representative cases out of 15 patients with 23 traumatized teeth treated to date in our clinic are presented. None had labial bone fractures. The teeth were replaced with NobelReplace Groovy implants (Nobel Biocare, Gothenburg, Sweden) in the fresh sockets immediately after extraction. They were placed toward the palatal areas in the sockets and 3 mm below the gingival m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
0
6
0
1
Order By: Relevance
“…Increased free radical oxidation in the blood was not limited to lipid peroxidation and resulted in increased serum levels of carbonylated proteins. Facilitation of oxidative degradation of proteins in the blood was казанский медицинский журнал, 2015 г., том 96, №5 В связи с тем, что применение имплан-тов способствует наиболее физиологичному восстановлению функций зубочелюстной системы, повышению эффективности ор-топедического лечения, обеспечивает про-филактику деформаций зубных рядов и дисфункции височно-нижнечелюстного сустава, дентальная имплантация служит востребованным видом ортопедической по-мощи [7]. В то же время более чем у четверти пациентов после такого рода хирургических вмешательств в связи с травматизацией и раневым повреждением развиваются ослож-нения, сопровождающиеся возникновением боли, воспаления, комплекса других харак-терных для этой ситуации функциональ-ных и структурных нарушений, ухудшени-ем общего состояния и работоспособности [6].…”
Section: Features Of Free Radical Lipid Peroxidation and Serum Proteiunclassified
“…Increased free radical oxidation in the blood was not limited to lipid peroxidation and resulted in increased serum levels of carbonylated proteins. Facilitation of oxidative degradation of proteins in the blood was казанский медицинский журнал, 2015 г., том 96, №5 В связи с тем, что применение имплан-тов способствует наиболее физиологичному восстановлению функций зубочелюстной системы, повышению эффективности ор-топедического лечения, обеспечивает про-филактику деформаций зубных рядов и дисфункции височно-нижнечелюстного сустава, дентальная имплантация служит востребованным видом ортопедической по-мощи [7]. В то же время более чем у четверти пациентов после такого рода хирургических вмешательств в связи с травматизацией и раневым повреждением развиваются ослож-нения, сопровождающиеся возникновением боли, воспаления, комплекса других харак-терных для этой ситуации функциональ-ных и структурных нарушений, ухудшени-ем общего состояния и работоспособности [6].…”
Section: Features Of Free Radical Lipid Peroxidation and Serum Proteiunclassified
“…4 Still others have suggested that an immediate implant technique is more challenging, both surgically and prosthetically, compared to delayed placement techniques and the reduced success represents a learning curve for the more difficult procedure. 10 In some cases, immediate implant placement is the consequence of a traumatic dental injury, which by itself can increase the risk of the surgical complications, 11 including infection. The role of infection in immediate implant failure is disputed, however.…”
Section: Introductionmentioning
confidence: 99%
“…e development of implantology urges the specialists to reduce the time of implant integration and prosthetic procedures and to quickly and successfully restore the patient [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%